The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1021/es049251o
|View full text |Cite
|
Sign up to set email alerts
|

Water Purification from Organic Pollutants by Optimized Micelle−Clay Systems

Abstract: Removal of anionic pollutants (imazaquin, sulfentrazone, sulfosulfuron) and neutral pollutants (alachlor, acetochlor, chlorotoluron, bromacil) from water by micelles preadsorbed on montmorillonite was studied. Micelles of octadecyltrimethylammonium and benzyldimethylhexadecylammonium (BDMHDA) were used. The micelle-clay systems (1% w/w) removed 87-99% of the pollutants from their water solutions containing 1-33 mg/L of herbicide. The nature of the headgroup of the organic cation, which forms the micelles, is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 17 publications
3
85
2
Order By: Relevance
“…The adsorption of ODTMA added at concentrations above the CMC (i.e., as micelles) on montmorillonite was complete, even at high initial organic cation concentrations reaching adsorption of 150% of the CEC. Complete adsorption of ODTMA micelles by montmorillonite has been previously shown [39,40].…”
Section: Adsorption Of Organic Cations On Montmorillonite and Zeta Pomentioning
confidence: 89%
“…The adsorption of ODTMA added at concentrations above the CMC (i.e., as micelles) on montmorillonite was complete, even at high initial organic cation concentrations reaching adsorption of 150% of the CEC. Complete adsorption of ODTMA micelles by montmorillonite has been previously shown [39,40].…”
Section: Adsorption Of Organic Cations On Montmorillonite and Zeta Pomentioning
confidence: 89%
“…Allophane is therefore available for removal of the micelles consisting of anionic surfactants and fats from aqueous phase. In previous studies, some hydrophobic pollutants were removed from water using the layered clay minerals such as montmorillonite and kaolinite hydrophobically modified with the surfactant molecules (Polubesova et al, 2004;Li and Gallus, 2005;Polubesova et al, 2005;Rodoríguez-Cruz et al, 2005;Zadaka et al, 2007;Sánchez-Martín et al, 2008). In addition, the clay minerals adsorbed the micelles formed by adding the surfactant molecules to the polluted water (Polubesova et al, 2004;Polubesova et al, 2005;Zadaka et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Polubesova et al (2005) investigated the removal of anionic pollutants (imazaquin, sulfentrazone, and sulfosulfuron) and neutral pollutants (alachlor, acetochlor, chlorotoluron, and bromacil) from water by micelles of octadecyltrimethylammonium and benzyldimethylhexadecylammonium (BDMHDA) preadsorbed on montmorillonite. Their results indicated that 87-99 % of the pollutants were removed from aqueous phase.…”
Section: Influence Of Colloids On the Environmental Behaviors Of Pcs mentioning
confidence: 99%